Use of visual spatial intelligence theory to improve the english vocabulary acquisition in 5th graders at unidad educativa ecomundo Babahoyo during the school year 2017 – 2018 - Díaz Ronquillo, Nidia Lilibeth (2019)
During decades, Teachers have been researching the main problem in teaching and learning process in order to get the students’ attention and improve the English language acquisition. Visual Spatial intelligence is defined as the ability to recognize and elaborate visual images, distinguish through sight specific features of objects, make mental images; it is also known as the reasoning about space and its dimensions, handling and reproduction of internal or external images. The present investigation was based on the study of visual-spatial in the development of English vocabulary acquisition, in fifth graders at Unidad Educativa ECOMUNDO in the capital of Los Rios in Babahoyo city. The development of oral language communication and vocabulary skills will be possible thanks to the use of visual-spatial intelligence through the use of different visual methods such as audiovisual activities, songs, the interpretation of pictures, and other pedagogical resources……….